2022
DOI: 10.3389/fgene.2022.940776
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional analysis of novel SOX11 variants in Chinese patients with Coffin-Siris syndrome 9

Abstract: SOX11 is a transcription factor belonging to the sex determining region Y-related high-mobility group box family that plays a vital role in early embryogenesis and neurogenesis. De novo variants in SOX11 have been initially reported to cause a rare neurodevelopmental disorder, mainly referred to Coffin-siris syndrome 9 (CSS9, OMIM# 615866) which is characterized with growth deficiency, intellectual disability (ID), microcephaly, coarse facies, and hypoplastic nails of the fifth fingers and/or toes. A recent la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Literature deals with a total of 82 subjects with pathogenic variants in SOX11 , including complete gene deletions (14%), missense (74%) and loss‐of‐function (12%) variants 4,5,7–19 . Detailed clinical information and clinical pictures were available for 32/82 subjects, including our patient.…”
Section: Resultsmentioning
confidence: 99%
“…Literature deals with a total of 82 subjects with pathogenic variants in SOX11 , including complete gene deletions (14%), missense (74%) and loss‐of‐function (12%) variants 4,5,7–19 . Detailed clinical information and clinical pictures were available for 32/82 subjects, including our patient.…”
Section: Resultsmentioning
confidence: 99%
“…(2) Compared with prior CSS-9-related publications including nonsystematic literature review (Alburaiky et al, 2022;Al-Jawahiri et al, 2022;Diel et al, 2021;Ding et al, 2022;Hanker et al, 2022;Khan et al, 2018;Okamoto et al, 2018;Wakim et al, 2021), we did a systematic literature review in this study on reported CSS-9 cases and found that pathogenic SOX11 SNVs altering the HMG domain were more likely to cause the widest range of organ anomalies, reminding patients carrying those variants should be aware of potential risks of having multiple organ anomalies and need thorough clinical examination.…”
Section: Discussionmentioning
confidence: 99%
“…Since two SOX11 pathogenic SNVs were first identified by Tsurusaki et al (2014) to associate with CSS‐like phenotypes, many SOX11 pathogenic SNVs have been reported and the phenotypic spectrum of CSS‐9 has been further expanded (Alburaiky et al, 2022; Al‐Jawahiri et al, 2022; Cho et al, 2022; Diel et al, 2021; Ding et al, 2022; Hanker et al, 2022; Hempel et al, 2016; Khan et al, 2018; Okamoto et al, 2018; Tsurusaki et al, 2014; Wakim et al, 2021; Wang et al, 2023). Given the high variability of these phenotypes and multiple organ anomalies related to CSS‐9, it is obvious that CSS‐9 is an untypical subtype of CSS with increased heterogeneous phenotypes; new reports of CSS‐9 cases could identify further phenotypes related to this syndromic condition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations